MOTHERHOOD AS A HISTORICAL PHENOMENON IN THE CONTEXT OF THE NORTH CAUCASUS: METHODOLOGICAL ASPECT - E. M. Marchenko (Гуманитарные и юридические исследования)
The article is an attempt to apply psycho-historical method and an interdisciplinary approach to analysis of the practices of perception and regulation of motherhood in different ethnic and religious communities of the North Caucasus. Using the concept of “maternity” the author examines ethical, traditional and legal methods of regulation of maternal behavior, as well as allocates general and specific methods and practices which were typical of different national traditions of the region. The article examines the factors contributing to the transformation of traditional methods and assessments of motherhood, and identifies main areas of the evolution of the phenomenon.